The National Tendencies in Lithuanian Interwar Interior Design (1918–1940) - Preišegalavičienė, Lina (Załącznik Kulturoznawczy, 2019)
After proclaiming independence in 1918, one of the most important tasks was creation of new visual-architectural and design identity which was called ‘Lithuanian Style’ or ‘National Style’. That search for a new image had to be established by an intentional, wilful act which could be able to create a desired object in accordance with the pre-planned model. Because of the multi-national origin of the artists, their distinct education in various countries (Germany, Italy, Poland, Russia, etc.), and the multiculturalism of customers, the same idea of countries’ identity was realised in very different visual forms. This variety of Lithuanian interior design approaches was strived to be untangled for the first time in the scientific monograph Lithuanian Interwar Interiors 1918–1940. Meanwhile, the current article (due to the space limit) presents the idea of national tendencies in the interior design. The latter prompts the understanding that theoretical formulation of Lithuanian National Style was ultrarational, attractive, and suitable for different aesthetic tastes – above all, it truly represented various social strata and nations living in Lithuania at that time.